Time to Death and Its Determinant Factors Among Patients With Chronic Heart Failure in Northwest Ethiopia: A Retrospective Study at Selected Referral Hospitals - Moyehodie, Yikeber Abebaw; Muluneh, Mitiku Wale; Belay, Alebachew Taye; Fenta, Setegn Muche (Frontiers in Cardiovascular Medicine, 2022)
Background: Heart failure is a major health problem that affects patients and healthcare systems worldwide. It is the leading cause of morbidity and death and negatively impacts quality of life, health care costs, and longevity. However, the causes of death were not well defined. This study aimed to identify the determinant of death among heart failure patients in Amhara Region, Northwest Ethiopia. Methods: A multicenter retrospective cohort study was conducted on 285 patients with age group 15 or older under follow-up from January 2015 to December 31, 2019. Descriptive analyses were summarized using the Kaplan-Meier survival curve and the log-rank test. Then, the Cox-proportional hazard regression model was employed to estimate the hazard of death up to five years after they were admitted to the heart failure department to follow-up their treatment. Results: Out of 285 heart failure patients 93(32.6%) of the respondents were dying within five years of follow-up. Anemia was the commonly comorbid disease (30.5 %), and valvar heart disease was the commonest etiology (33.7%) of chronic heart failure in this study. This study showed a significant mortality difference between hospitals. Heart failure patients with hypertension (AHR: 3.5076, 95% CI: 1.43, 8.60), anemia (AHR: 2.85, 95% 1.61, 5.03), Pneumonia (AHR: 2.02, 95% 1.20, 3.39), Chronic Kidney Disease (2.23, CI: 1.31, 3.77), Diabetic Multiuse (AHR: 2.42, 95% CI: 1.43, 4.09) were having more hazard of death. Moreover, New York Heart Association Class (III and IV), Etiology (Ischemic Heart Disease and unknown etiology), male gender (AHR: 2.76, 95%:1.59, 4.78), and high pulse rate (AHR: 1.02, 95%:1.00, 1.04) were at higher risk of death. Conclusion: There was a mortality difference between hospitals. The study has revealed that heart failure patients' who had anemia, diabetic multiuse, pneumonia, hypertension, Chronic Kidney Disease, and etiology, severe New York Heart Association Class (III and IV), male gender, and high pulse rate were main factors associated with death. Health professionals could give more attention to the patients whose pulse rate is high, male gender, and a patient who had comorbidities in the ward.